Mothers' and Daughters' Perceptions of the Role of the Counsellor - Laughren, Mary E.; Herman, Al (Revue canadienne de counseling et de psychothérapie, 2012)
This study investigated differences between daughters' and their mothers' perceptions of the role of the school counsellor. The subjectswere asked to respond to a questionnaire designed to test the appropriateness of different problem areas for discussion with a counsellor. Significant differences in perceptions of counsellor role between daughters and their mothers were indicated. Educational and vocational problem areas were viewed by both daughters and mothers as the most suitable areas in which to seek counsellor help.